2008
DOI: 10.1002/em.20397
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos‐induced DNA damage in rat liver and brain

Abstract: Chlorpyrifos (O,O'-diethyl-O-3,5,6-trichloro-2-pyridyl phosphorothionate, CPF) is a broad spectrum organophosphate pesticide used to control a variety of pests. The present study was undertaken to test the in vivo genotoxic potential of CPF in rats, using the single cell gel electrophoresis (or comet) assay. The rats were administered 50 mg and 100 mg CPF/kg body weight daily for 1, 2, and 3 days as well as 1.12 mg and 2.24 mg CPF/kg body weight for 90 days. The level of DNA damage was estimated by scoring 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 39 publications
1
35
0
2
Order By: Relevance
“…Several in vivo and in vitro studies reported that the genotoxicity of OPs such as dimethoate, methyl parathion, chlorpyrifos, phorate, and malathion in hepatocytes was associated with oxidative damage (130,131,127,(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159). A study by Hreljac et al (160) showed that methyl paraoxon was less genotoxic in HepG2 cells than its parent OP methyl parathion.…”
Section: Possible Mutagenic Genotoxic and Carcinogenic Effects Of Opsmentioning
confidence: 99%
“…Several in vivo and in vitro studies reported that the genotoxicity of OPs such as dimethoate, methyl parathion, chlorpyrifos, phorate, and malathion in hepatocytes was associated with oxidative damage (130,131,127,(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159). A study by Hreljac et al (160) showed that methyl paraoxon was less genotoxic in HepG2 cells than its parent OP methyl parathion.…”
Section: Possible Mutagenic Genotoxic and Carcinogenic Effects Of Opsmentioning
confidence: 99%
“…pneumonocytes (Byrne et al, 1998;Bomser and Casida, 2001;Tian and Yamauchi, 2003). Exposure to chlorpyrifos, acutely or chronically, caused a dose-dependent increase in DNA damage in the liver and brains of rats, and also the production of reactive oxygen species that caused considerable cytotoxicity in PC12 cells (Mehta et al, 2008;Crumpton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Animal and human studies do support that OPs may be associated with these outcomes (Bouchard et al, 2010; Eskenazi et al, 2007; Furlong et al, 2014; Middlemore-Risher et al, 2010; Ricceri et al, 2003, 2006). Other biological mechanisms, such as oxidative stress (Soltaninejad and Abdollahi, 2009), DNA damage (Mehta et al, 2008), and long lasting impacts on the dopaminergic systems (Aldridge et al, 2005b), may have downstream effects on a variety of outcomes that could coalesce into a phenotypic presentation of traits.…”
Section: Introductionmentioning
confidence: 99%